2020
DOI: 10.17573/cepar.2020.1.06
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Public Governance Practices for Business R&D Activity in the EU

Abstract: The public sector and public governance play a crucial role in the contemporary society which takes care of social needs. Therefore, it is not surprising that good governance has often been used to explain good economic performance as well as the well-being of a society over the last decade. However, the business sector often represents a channel through which public governance affects economic performance, which has largely been neglected in the existing literature. In this context, not much is known about th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…This is especially emphasized in the public sector as one of the largest producers of information and services in public administration. Therefore, public administration should pursue modern public governance practices (Ravšelj and Hodžić, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This is especially emphasized in the public sector as one of the largest producers of information and services in public administration. Therefore, public administration should pursue modern public governance practices (Ravšelj and Hodžić, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…As the comparative analyses and researches (e.g., [2,14,[59][60][61][62]) presented without necessary financial resources, both from the government and the business enterprise sector, it may not be expected that R&D will bring knowledge, innovations, and technologies competitive on an international level, which will increase productivity, employment rate, and economic competitiveness. According to Hu, Yang, and Chen [26], intellectual property rights protection, technological co-operation among business sectors, knowledge transfer between business sectors and higher-education institutions, agglomeration of R&D facilities, and involvement of the government sector in R&D activities significantly improve national R&D efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors deal with a status and a significance of public and private sectors in research and development, a mutual relationship of both sectors, the role of research institutions, influence of public and private resources that support research, development, and innovation activities, or the linkages between technology and public science [2,14,24,25]. Ravselj and Hodzic [26] showed that not much is known about the role of public governance in promoting research and development (R&D) in the business sector in the EU. The authors aimed to explain the interaction between the public and business sectors in a cross-national setting by investigating the relationship between different public governance practices and business R&D activity.…”
Section: Introductionmentioning
confidence: 99%
“…This can partly be attributed to the existence of significant obstacles to the entry of new employees and growth, which is characteristic for most economies. Smaller companies are faced with disproportionately greater regulatory barriers compared to larger companies (Aristovnik and Obadić, 2015), and inefficient public administration, weak judicial capacity and legal uncertainty remain the main obstacle to industrial competitiveness and economic growth in EU member states (European Commission, 2014; Ravšelj and Hodžić, 2020). In this paper, we concentrate on administrative barriers that SMEs are facing in two new EU countries, because in many cases, private business in transition countries must struggle with governmental interference, corruption and environmental changes on a much larger scale than in advanced western economies (Aidis, 2005).…”
Section: Significance Of Small and Medium-sized Enterprises In The Eumentioning
confidence: 99%